Applying Finite State Automata to Structural Design of an Automatic Ice Cream Machine - Novilia Lestari; Sri Wahyu; Melisa Sartika; Annisa Thurrabiah Khanza; Sadra Afifah; Ade Candra Bayu (Journal of Applied Mathematics and Modelling, 2025)
Technological advances encourage the implementation of automated machines to improve efficiency and process consistency, one of which is in automatic ice cream machines. These machines require a structured control system to manage the ordering flow and user interaction. This study aims to apply Automata theory, specifically Finite State Automata (FSA), to systematically model the working logic of an automatic ice cream machine. The system workflow is represented using Non-Deterministic Finite Automata (NFA) which includes the stages of cup size selection, flavor selection, topping selection, payment process, and order confirmation. This system allows the selection of 3 cup sizes: small, medium, and large, ensuring that each ordering process begins with an explicit cup size selection before the user proceeds to the next stage. Also, at the topping selection stage, the automata model is designed to be more flexible by providing transitions that allow users to choose no topping at all or to choose more than one topping. Model validation was carried out through simulations using JFLAP. The simulation results show that the model can accept valid input sequences and reject invalid inputs, so that the system flow runs consistently. Thus, FSA is proven effective as a formal framework in modeling and analyzing automatic ice cream machine systems.